2012
DOI: 10.5194/amt-5-1229-2012
|View full text |Cite
|
Sign up to set email alerts
|

A gas chromatographic instrument for measurement of hydrogen cyanide in the lower atmosphere

Abstract: Abstract. A gas-chromatographic (GC) instrument was developed for measuring hydrogen cyanide (HCN) in the lower atmosphere. The main features of the instrument are (1) a cryogen-free cooler for sample dehumidification and enrichment, (2) a porous polymer PLOT column for analyte separation, (3) a flame thermionic detector (FTD) for sensitive and selective detection, and (4) a dynamic dilution system for calibration. We deployed the instrument for a ∼4 month period from January-June, 2010 at the AIRMAP atmospher… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 55 publications
1
2
2
Order By: Relevance
“…Excluding the BBP, the mean ambient HCN concentration of 35 ppt and maximum concentration of 132 ppt is comparable with other ground-based HCN measurements, both rural and urban (Ambrose et al, 2012;Knighton et al, 2009). The species with the highest correlations with HCN with the BBP removed are propanoic acid (R 2 = 0.79), HONO (R 2 = 0.76), MIC (R 2 = 0.75), formamide (R 2 = 0.71), and N-methylformamide (R 2 = 0.68).…”
Section: Identification and Behavior Of Key Speciessupporting
confidence: 79%
“…Excluding the BBP, the mean ambient HCN concentration of 35 ppt and maximum concentration of 132 ppt is comparable with other ground-based HCN measurements, both rural and urban (Ambrose et al, 2012;Knighton et al, 2009). The species with the highest correlations with HCN with the BBP removed are propanoic acid (R 2 = 0.79), HONO (R 2 = 0.76), MIC (R 2 = 0.75), formamide (R 2 = 0.71), and N-methylformamide (R 2 = 0.68).…”
Section: Identification and Behavior Of Key Speciessupporting
confidence: 79%
“…Consistent with our low HCN measurements, the authors found that HCN mixing ratios only spiked above the FTIR method detection limit of 3.2 ppbv on three occasions (isolated 1 min data points). Although prior measurements seem exceptionally high, our measurements are also on the low end of those reported for ground-level, ambient HCN in a rural region with little forest fire impact, which are on the order of a few hundred pptv (Ambrose et al, 2012). No significant long-term changes have been observed or expected for tropospheric HCN (Zhao et al, 2002) so it is unclear as to why the present measurements are so low.…”
Section: Overview Of Mobile Pollutant Measurementscontrasting
confidence: 56%
“…Consistent with our low HCN measurements, the authors found that HCN mixing ratios only spiked above the FTIR method detection limit of 3.2 ppbv on three occasions (isolated 1 min data points). Although prior measurements (Moussa et al, 2016) seem exceptionally high, our measurements are also on the low end of those reported for ground-level, ambient HCN in a rural region with little forest fire impact, which are on the order of a few hundred pptv (Ambrose et al, 2012). No significant long-term changes have been observed or expected for tropospheric HCN (Zhao et al, 2002) so it is unclear as to why the present measurements are so low.…”
Section: Overview Of Mobile Pollutant Measurementscontrasting
confidence: 62%